The relationship between serve-receive quality and attack performance across different age categories in women's elite volleyball - Adamec, P.; Pridal, V. (Journal of Physical Education and Sport, 2024)
The objective of this study was to examine and compare the potential correlation between serve-reception and subsequent attack effectiveness among senior, U20 and U18 age groups in top-level women's volleyball. The study focused on senior national women's teams participating in the 2023 European Championship in Group D and the U20 and U18 teams participating in the 2024 European Championship qualification rounds. A total of 1,967 attacks across 84 sets in 22 matches were analyzed. Data were collected using the specialized Data Volley Professional 3.2.1. software. The Chi-Square Test and contingency coefficient C were utilized to identify associations, while the Z-test was employed to ascertain differences in attack quality following accurate and inaccurate serve-reception across various skill levels. The results were evaluated at the 5% statistical significance level. We found a statistically significant relation (p<0.05) across all studied age categories (U18 X2 = 38.6463, C=0.1211; U 20 X2 = 13.0766, C=0.1458; senior women X2 = 62.5291, C=0.3069). The results of the statistical analysis confirmed the assumption of a higher incidence of excellent attack after a positive serve-reception in all the studied categories compared to attacks after a negative serve-reception. Statistically significant differences were also found in most other levels of attack quality assessment (p<0.05), except for erroneous attacks, where we found no significant differences in attack after positive and negative serve-reception in all of the categories examined (p>0.05). Statistically insignificant differences were found for positive attacks (+) in the U20 and U18 categories (p>0.05). The contingency coefficient of senior females was the highest (45%) of all the possible coefficients in the given contingency table (Cmax = 0.86602), while it was 27% for the U20 and 19% for the U18 category. These results suggest a decreasing closeness of the relation between serve-receive accuracy and the qualitative characteristics of the subsequent attacking stroke from the oldest age category to the youngest one, thus confirming our hypothesis. The results can be useful in evaluating the performance of players in matches and serve as model characteristics of the team's play in side-out transition in the studied age categories.